Radiografia di una generazione: giovani e disuguaglianza negli anni Sessanta e Settanta (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
The essay first analyses sociological surveys on young people conducted in the 1960s and 1970s and shows how these surveys generally projected the expectations of the post-war generation onto the baby boomers and viewed young people within their social class, reflecting a static conception of social mobility. Secondly, the essay highlights how 1968 came largely unexpected and brought the issue of young people's expectations to the fore, while also reviving the controversy over the university as a place for the creation of the intellectual proletariat. After 1968, youth unemployment and social mobility became recurring themes in public debate.